Population Structure of Putat Laut (Barringtonia asiatica (L.) Kurz) in the Tabanio Mangrove Area, Tanah Laut Regency - Nurmina Nurmina; Dharmono Dharmono (Universitas Khairun, 2026)
The population structure of plants is one of the areas of study in ecology that discusses the presence of a group of plants within a particular area. The Sea Poison Tree (Barringtonia asiatica (L.) Kurz) was found in the mangrove area of Tabanio, Tanah Laut Regency. This study aims to examine the population structure of the Sea Poison Tree in the Tabanio mangrove area of Tanah Laut Regency. The method used in this research was a total exploration survey. The results showed that the population structure of the Sea Poison Tree in the Tabanio mangrove area consisted of 18.55 individuals/km² in the pre-reproductive phase, 27.67 individuals/km² in the reproductive phase, and 11.07 individuals/km² in the post-reproductive phase, forming a disrupted vase- or urn-shaped pyramid. Based on these findings, the Sea Poison Tree can be categorized as being in a safe and fairly developed condition, as the number of mature individuals exceeds 25 individuals per square kilometer.